AN IMPROVED METHOD TO PRODUCE ROOTED SEEDLINGS FROM TPS IN THE HIGHLANDS OF UZBEKISTAN - Carli, C.; Khalikov, D.; Rasulov, A I (Potato Journal, 2013)
In uzbekistan, farmers struggle to obtain high quality seed potatoes at affordable prices. price of imported seed has risen sharply in recent years compelling farmers to utilize their own saved seed more frequently with declining potato yields due to seed-borne diseases. in an effort to develop research on seed systems, cip has focused the development of new techniques and practices for the informal seed system. a technique for seed potato production has been tested to produce rooted seedlings from Tps (true potato seed) under nurseryÂ conditions. This technique has the advantage of producing stronger rooted seedlings with substrate intimately attached to the rooting system, thus improving survival rates and considerably reducing transplanting shock and root damage. This method is extremely simple, cheap, and offers an alternative activity to smallholders who are familiar with vegetable growing and who live in marginal areas. The only drawback to the adoption of this alternative method may be the longer duration of the growing cycle of the tested Tps families that would need to be shortened, requiring, therefore, the supply of new Tps materials.